Novel Coumarin 7-Carboxamide/Sulfonamide Derivatives as Potential Fungicidal Agents: Design, Synthesis, and Biological Evaluation - Shu-Guang Zhang; Yu-Qiang Wan; Ya Wen; Wei-Hua Zhang (Molecules, 2022)
Coumarin compounds have a variety of biological activities such as anti-tumor, anti-coagulation, anti-HIV, anti-fungal, and insecticidal. Amide and sulfonamide compounds have been used as fungicides for half a century, and dozens of varieties have been developed so far. This study focused on the introduction of carboxamide and sulfonamide moieties in a coumarin core to discover novel derivatives. Based on this strategy, we synthesized two series of novel carboxamide and sulfonamide substituted coumarin derivatives, and their fungicidal activity was also investigated. Some designed compounds possessed potential activities against six phytopathogenic fungi in the primary assays, highlighted by compound 6r. Compound 6r exhibited stronger fungicidal activity against Botrytis cinerea (EC50 = 20.52 µg/mL) and will be the lead structure for further study.